PEMANFAATAN BUAH LOKAL SEBAGAI UPAKARA DAN UPAYA PELESTARIANNYA - Kadek Yuniari Suryatini; Anak Agung Ayu Putriningsih; I Gusti Agung Gede Wiadnyana; Ni Made Milati (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2023)
. Hindu religious ceremonies in Bali always use upakara or banten as a means of getting closer to Ida Sang Hyang Widhi Wasa. Plants are one of the ceremonial equipment in the form of leaves, fruit, and flowers. The use of fruit, especially local fruit, has an important meaning in making upakara. Among the various types of fruit, some of them can be found easily, but some are rarely found so they are considered rare. Based on these facts, various efforts are needed to preserve it. Preserving local fruit can be done by: limiting imported fruit and preferring to consume local fruit to prevent extinction; cultivating or multiplying local fruit plants; not cutting down local fruit trees carelessly; applying the principles of logging and planting; and maintaining plants and care for them properly. Another effort is local wisdom which is spread through myths and folklore. The use of plant species, including fruit, in ceremonies provides a mandate or message of responsibility for preserving plants so that the ceremony can continue.